2019
DOI: 10.22435/jek.18.1.1777.60-69
|View full text |Cite
|
Sign up to set email alerts
|

Pelayanan Pemeriksaan Kehamilan Berkualitas Yang Dimanfaatkan Ibu Hamil Untuk Persiapan Persalinan Di Indonesia

Abstract: Antenatal care (ANC) is a prevention healthcare for maternal health and their babies. In order to fulfill the needs of them, an accessible health facility that provides ANC with qualified services for the community is needed. This study aims to determine the utilization of maternal health services as preparation for safe delivery. Analysis of this study used the data from National Health Indicator Survey (Sirkesnas) 2016 and Village Potential Census (Podes) 2014. The analysis technique was multivariable logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
0
5
0
17
Order By: Relevance
“…In Indonesia, health and nutrition counselling for pregnant women is a part of integrated antenatal care service besides anthropometric measurements, BP check, tetanus vaccine, iron tablet supplementation, biochemical assessment, and examination of fundal height, foetal location and pulse, as well as specific case management. 20 The topics of counselling might vary from maternal nutrition to breastfeeding. 21,22 A previous study in Indonesia showed that breastfeeding counselling during antenatal care p e r i o d c o u l d i n c r e a s e t h e p r a c t i c e o f breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, health and nutrition counselling for pregnant women is a part of integrated antenatal care service besides anthropometric measurements, BP check, tetanus vaccine, iron tablet supplementation, biochemical assessment, and examination of fundal height, foetal location and pulse, as well as specific case management. 20 The topics of counselling might vary from maternal nutrition to breastfeeding. 21,22 A previous study in Indonesia showed that breastfeeding counselling during antenatal care p e r i o d c o u l d i n c r e a s e t h e p r a c t i c e o f breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…ASEAN Millenium Development Goals (MDGs) tahun 2017 menyebutkan AKI di Indonesia tahun 2015 sebesar 305/100.000 kelahiran hidup dan menjadikan Indonesia dengan peringkat AKI tertinggi kedua di Asia Tenggara. Peringkat pertama diduduki Laos (Dharmayanti et al, 2019).…”
Section: Pendahuluanunclassified
“…Besaran risiko yang juga cukup besar didapat dari hasil penelitian Bunga dkk 18 yang menyebutkan bahwa bayi yang lahir prematur berhubungan dengan kejadian hipertensi dalam kehamilan ibunya dan berisiko sebanyak 9,75 kali dibandingkan dengan yang normal. Besarnya kejadian hipertensi yang terjadi di Indonesia memungkinkan karena kurangnya kesadaran ibu dalam melakukan antenatal care (ANC) yang berkualitas sehingga komplikasi yang terjadi lambat teridentifikasi oleh petugas kesehatan, seperti hasil penelitian yang dilakukan oleh Dharmayanti dkk 27 yang menyebutkan bahwa persentase ibu yang melakukan pemeriksaan kehamilan lengkap 7-10T dengan frekuensi K4 ideal hanya sebesar 2%. Selain itu perlu diperhatikan juga kualitas dari tenaga kesehatan terutama bidan karena berdasarkan hasil penelitian yang dilakukan Hendrawan dkk 28 menyebutkan bahwa bidan yang melakukan ANC lengkap 9T adalah 18,8% dan hanya 20,4% puskesmas yang memiliki sarana dan prasarana yang diperlukan untuk pelayanan ANC secara lengkap.…”
Section: Pembahasanunclassified